Anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor 2 encephalitis with olfactory hallucination: a case report and literature review - Wang, Xuyi; Zhao, Chenxi; Chen, Qinghua; Yu, Weitong; Zhao, Siyu; Wang, Pin; Sun, Lin; Xu, Linlin; Xu, Yingying (Frontiers in Immunology, 2025)
Anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis is a rare autoimmune disease divided into two subtypes, anti-AMPAR1 encephalitis and anti-AMPAR2 encephalitis, depending on the presence of autoantibodies targeting the GluR1 and GluR2 subunits of the AMPA receptor. The main manifestations are limbic encephalitis, including cognitive impairment, seizures, and psychiatric symptoms. The reported cases of anti-AMPAR encephalitis have grown; however, no research has yet described the clinical characteristics of each subtype. Herein, we present a case of a middle-aged woman with anti-AMPAR2 encephalitis who was admitted to the hospital with sudden-onset seizures. The physical examination did not show noteworthy findings, but the auxiliary examination revealed abnormalities in the temporal lobe. On the third day of her hospitalization, she experienced olfactory hallucinations. AMPAR2 antibodies were detected positive in both serum and cerebrospinal fluid (CSF). After receiving a combination of glucocorticoids and intravenous immunoglobulin (IVIG) treatment, the patient was discharged with improved symptoms. She maintained her regimen of oral prednisone and gradually reduced the dosage following her discharge from the hospital. After 6 months, she was readmitted to the hospital due to a headache and a positive IgG test for serum AMPAR2 antibodies. The patient’s symptoms resolved with glucocorticoid treatment. Additionally, we conducted a literature review and gathered data from 37 individuals with anti-AMPAR2 encephalitis, including our present case. The patients had different levels of AMPAR2 antibodies in their CSF or serum, and some also had other antibodies. There were 23 female and 14 male patients, with a median age of 47 years. Of the patients, 19 (51%) had a history of tumors. The predominant clinical symptoms were memory impairment (78%) and psychobehavioral abnormalities (70%), with other symptoms such as epilepsy, disorders of consciousness, disorientation, hallucinations, dyskinesia, sleep disorders, and cerebellar signs. Most patients exhibited abnormalities on cerebral magnetic resonance imaging (MRI), electroencephalogram (ECG), and CSF examination. Therapeutic interventions such as steroids, IVIg, plasma exchange, or immunosuppressants led to symptom alleviation in the majority of patients. Nevertheless, some patients did not exhibit notable progress or died. This report summarized the clinical features of patients with anti-AMPAR2 encephalitis and discussed its pathogenesis to facilitate early recognition and management.